Concrete fracture a multiscale approach - Mier, J. G. M. van (CRC Press, 2013)
The study of fracture mechanics of concrete has developed in recent years to the point where it can be used for assessing the durability of concrete structures and for the development of new concrete materials. The last decade has seen a gradual shift of interest toward fracture studies at increasingly smaller sizes and scales